Polymorphisms of CYP1A1*4 and GST as Susceptibility and Prognostic Genes for Acute Myeloid Leukemia - M, Heba; A, Ahmed; E, Sheriff (IIUM Medical Journal Malaysia, 2010)
Introduction: Associations between polymorphisms for genes encoding enzymes involved in biotransformation of xenobiotics and susceptibility to several cancers have been shown in several studies. The aim of the study is to investigate the influence of cytochromes P450 (CYP1A1*4) and Glutathione S-transferases (GSTs) (T1 and M1) gene polymorphisms in susceptibility to acute myeloid leukemia (AML) as well as their prognostic role for the treatment outcome in AML patients. Material and Methods: This study included 65 individuals classified as healthy controls and newly diagnosed AML patients. BMA and immunophenotyping assay by flowcytometry were done at D1 and D14 following treatment induction to assess the complete remission or non response to treatment in AML patients. The CYP1A1*4 and of GSTT1and GSTM1 genotypes were examined using polymerase chain reaction (PCR)-based methods. Results: A higher prevalence of the CYP1A1*4 (CA and AA) genotype was found in AML patients than in controls (37% vs 23.3%, OR =3.25, 95% CI. 1.01-10.46, p=0.05). GSTT1 null genotype were also more frequent in AML patients than in controls (58% vs 26.7%, OR = 3.79, 95% CI 1.11-12.87, p=0.03). The combination of GSTT1 null genotype and CYP1A1 *4 (AA) genotype further increased the risk of AML (OR =12.66, 95% CI 1.19-128.6, p=0.03. Conclusion: GSTT1 null genotype appears to modulate individual’s susceptibility of AML patients to treatment response, especially when combined with CYP1A1*4 (AA) genotype suggesting gene-gene interactions.